1988
DOI: 10.1128/jcm.26.10.2139-2143.1988
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a bovine rotavirus with a "super-short" RNA electrophoretic pattern from a calf with diarrhea

Abstract: A rotavirus with a "super-short" RNA electropherotype was isolated from a calf with diarrhea and was designated VMRI strain. Segments 10 and Il of this rotavirus migrated more slowly than did those of bovine rotavirus strains NCDV, B641, and B223. The electrophoretic pattern of the VMRI strain was similar to that reported for rotaviruses with super-short RNA electropherotypes from humans and rabbits. Northern (RNA) blot hybridization indicated that gene 11 of the VMRI strain was altered and migrated between ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1990
1990
1996
1996

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…The results from PAGE analysis showing that none of the 25 PAGE positive samples had the vaccine virus electropherotype agreed with a previous report which suggested that the vaccine was probably not the cause of rotaviral diarrhea, and it was frequently inefficacious in preventing the infections in the herds [14]. Short electropherotype rotaviruses similar to the rotaviruses previously reported in humans, rabbits, pigs and calves [12][13][14][15][16][17][18][19] were found in all day 1 PAGE positive and most of day 7 PAGE positive samples obtained from calves while long electropherotype rotaviruses were found at days 7 and 14. Regardless of their electropherotypes, the presence of these short and long electropherotype rotaviruses might be due to their antigenic difference from common rotaviruses contaminating the farm environment; thus, they were able to evade passive immunity.…”
Section: Pagesupporting
confidence: 90%
See 2 more Smart Citations
“…The results from PAGE analysis showing that none of the 25 PAGE positive samples had the vaccine virus electropherotype agreed with a previous report which suggested that the vaccine was probably not the cause of rotaviral diarrhea, and it was frequently inefficacious in preventing the infections in the herds [14]. Short electropherotype rotaviruses similar to the rotaviruses previously reported in humans, rabbits, pigs and calves [12][13][14][15][16][17][18][19] were found in all day 1 PAGE positive and most of day 7 PAGE positive samples obtained from calves while long electropherotype rotaviruses were found at days 7 and 14. Regardless of their electropherotypes, the presence of these short and long electropherotype rotaviruses might be due to their antigenic difference from common rotaviruses contaminating the farm environment; thus, they were able to evade passive immunity.…”
Section: Pagesupporting
confidence: 90%
“…The high incidence of short electropherotype group A rotavirus in calves was unexpected. A few cases of short electropherotype and a mixture of short and long electropherotype rotaviruses were previously reported in diarrheic calves [12,13,15,16].…”
Section: Pagementioning
confidence: 89%
See 1 more Smart Citation
“…All bovine group A rotaviruses characterized thus far have the subgroup 1 antigen, and most exhibit a long RNA electropherotype pattern (143,144). Two recent studies have shown the occurrence of bovine group A rotaviruses with the subgroup 1 antigen and short electropherotype patterns (283,363). Short RNA electropherotype patterns had not been detected previously in bovine isolates but have been observed frequently in human rotavirus strains.…”
Section: Rotaviruses In Calves and Lambsmentioning
confidence: 92%
“…Viral RNA was extracted from fecal samples as previously described (Paul et al, 1988b ). Briefly, 0.2 g fecal samples were diluted with 0.6 ml of sodium acetate buffer, sonicated and clarified by centrifugation at 13 000Xg for 1 min.…”
Section: Purification Of Viruses and Extraction Of Nucleic Acidsmentioning
confidence: 99%